Ultra-open ventilated metamaterial absorbers for sound-silencing applications in environment with free air flows. (September 2020) - Xiang, Xiao; Wu, Xiaoxiao; Li, Xin; Wu, Peng; He, Hong; Mu, Qianjin; Wang, Shuxia; Huang, Yingzhou; Wen, Weijia
Abstract: High-efficiency absorption of low-frequency sounds (< 1000 Hz) while maintaining a free flow of fluids remains a significant challenge in acoustical engineering due to the rigid trade-off between absorption and ventilation performances. Although ongoing advances in acoustic metamaterials have unlocked unprecedented possibilities and various metamaterial absorbers have been proposed, most of them only work adequately in the condition of no sound transmissions. Unfortunately, such condition requires a complete block of fluid channels due to longitudinal nature of sounds, which allows them to penetrate any small holes. Otherwise, their absorption performance could be drastically degraded and often cannot exceed 50%. This basic trade-off between absorption and ventilation performances definitely constrains their applications in daily scenarios where free air flows are necessary. Though some ventilated sound barriers with large transmission loss have been demonstrated, they essentially only reflect sounds, which are still there and even may be reflected back. Here, to overcome this general difficulty, we propose and demonstrate an ultra-open ventilated metamaterial absorber. The absorber, aiming at low-frequency sounds, simultaneously ensures high-performance absorption and ventilation, confirmed in experiments. Their mechanism is understood from an effective model of coupled lossy oscillators. Furthermore, the absorbers can be simply stacked to work in a customized broadband, while maintaining a good ventilation. The demonstrated absorber provides a clear scheme for achieving high-performance absorption and ventilation at low frequencies, necessary for applications in environment with free air flows.